DEVELOPMENT OF POP-UP BOOK LEARNING MEDIA FOR NATURAL SCIENCE SUBJECTS IN CLASS III OF MADRASAH IBTIDAIYAH - Sulubere, Citra Amalia; Suwarno, Suwarno; Hidayat, Muhammad Almi (JMIE (Journal of Madrasah Ibtidaiyah Education), 2024)
Developing learning media is one of the teacher's efforts to achieve learning goals. In developing a learning media, appropriate procedures are needed to produce a product in the form of valid and effective learning media. The development of pop-up book media for science subjects was conducted to determine its feasibility based on the assessment of material experts and media experts, as well as wanting to know the effectiveness of pop-up book learning media for science subjects. This research uses development research with development procedures following the ADDIE model, which includes analysis, design, development, implementation, and evaluation steps. The research was carried out at MIN 1 Bener Meriah by taking samples from class 3. Data collection techniques used observation, interviews, questionnaires, documentation, and tests. Data analysis techniques include qualitative and quantitative data analysis. The findings of this research are: first, from the validity test by material experts, the results were 4.1 in the valid category, and second, from media experts, the results were 4.4 in the very valid category. Second, based on the effectiveness test using pretest and posttest techniques, the N-Gain test results were obtained at 0.61 with a moderate level of effectiveness, so it can be stated that the pop-up book learning media for science subjects is effective for use in learning. This research and development is still limited to MIN 1 Bener Meriah, so further research must be implemented in Madrasah Ibtidaiyah.